EVALUASI PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI DI KECAMATAN SIAK HULU KABUPATEN KAMPAR - ", FITRIANI; RUSLI, ZAILI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Poverty is one of the fundamental problems that become the center ofattention of the government in any country. One important aspect to support povertyreduction strategies is the availability of accurate data on poverty and on target. Goodpoverty data can be used to evaluate government policies on poverty , comparingpoverty across time and regions, as well as determining the target the poor with theaim of improving their condition. Poverty reduction by focusing on communityempowerment as the operational approach , commits the government in realizingwelfare for society. One of the poverty reduction program is Program NasionalPemberdayaan Masyarakat ( PNPM). To improve the effectiveness of povertyalleviation and job creation , the government launched Program NasionalPemberdayaan Masyarakat ( PNPM) started in 2007. These results indicate that theprogram in the district in the implementation of Siak Hulu has not done well.Implementation of empowerment that do still right on target, there are still poorpeople who have not been helped by the PNPM Mandiri , the poor economy is stilllow and should be considered as well as PNPM assistance in order to create wellbeingofsociety.Keywords : evaluation , input , policy process , output, outcome , impact damfeedback.